Foreign body in the tongue as a result of accidental gunshot from hunting rifle - Ratajek-Gruda, Monika; Strzelczyk-Sikorska, Olga; Janas-Naze, Anna (Journal of Education, Health and Sport, 2019)
Gunshots are one of the many causes of urgent admission of patients due to necessity of removing foreign bodies and bleeding control. A 63 y.o. patient was referred to the Department of Oral Surgery due to an accidental gunshot, which occurred in early adolescence and caused numerous post-gunshot injuries. The decision to waive surgical removal of foreign body was dictated by major risk of complications, such as: major bleeding from tongue vessels and probability of function loss. Also the lack of symptoms sustained such decision. Patient was informed about the necessity of performing the surgery in case of any pain, inflammation or necessity of proper interpretation of radiological examination (CT, MRI).